Grow first, gain fat in the meantime. Longitudinal study of anthropometric changes around menarche - Ziomkiewicz, Anna; Kozieł, Sławomir (Anthropological Review, 2015)
There is a long dispute among anthropologist over which factor is more important – skeletal maturation or energy accumulation – for menarche occurrence. Here we report results of longitudinal study conducted on the sample of 178 girls followed for the period from 2 years before to 2 years after the age of menarche. Each year during this period anthropometric measures of waist and hip circumference, pelvis breadth, subscapular, triceps and abdominal skinfold thickness were taken to document girls’ physical development. We found that changes in hip circumference and pelvis breadth were the most closely associated with menarche appearance. We also found that changes in anthropometric measures of lower body part preceded changes in anthropometric measures of upper body part and tended to peak one year before menarche occurrence while changes in upper body part tended to peak one year after menarche occurrence. These results suggest that both skeletal maturation and energy accumulation in the form of fat are equally important for menarche to occur. Furthermore, we are proposing a new indicator describing allometric changes of pelvis around menarche: hip circumference to pelvis breadth ratio (HCPBR).